Вплив технічного стану транспортних засобів на потік насичення - Гілевич, Володимир (Видавництво Львівської політехніки, 2018)
The analysis of methods of calculating the saturation flow has established that they do not take into account the technical condition of vehicles in transport flows. The expediency of taking into account the technical condition of vehicles in the calculation of the light cycle is shown.
Influence of the technical state of vehicles on the calculation of the saturation flow
Keywords: 656.13